Good arguments : how debate teaches us to listen and be heard - Seo, Bo (Penguin Press, 2022)
"When Bo Seo was 8 years old, he and his family migrated from Korea to Australia. At the time, he did not speak English, and, unsurprisingly, struggled at school. But, then, in fifth grade, something happened to change his life: he discovered competitive debate. Immediately, he was hooked. It turned out, perhaps counterintuitively, that debating was the perfect activity for someone shy and unsure of himself. It became a way for Bo not only to find his voice, but to excel socially and academically. And he's not the only one. Far from it: presidents, Supreme Court justices, and CEOs are all disproportionally debaters. This is hardly a coincidence. By tracing his own journey from immigrant kid to world champion, Seo shows how the skills of debating--information gathering, truth finding, lucidity, organization, and persuasion--are often the cornerstone of successful careers and happy lives. Drawing insights from its strategies, structure, and history, Seo teaches readers the skills of competitive debate, and in doing so shows how they can improve their communication with friends, family, and colleagues alike. He takes readers on a thrilling intellectual adventure into the eccentric and brilliant subculture of competitive debate, touching on everything from the radical politics of Malcolm X to Artificial Intelligence. Seo proves beyond a shadow of a doubt that, far from being a source of conflict, good-faith debate can enrich our daily lives and, indeed, is essential to a flourishing democracy"--